2019
DOI: 10.1101/781989
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

PARPi synthetic lethality derives from replication-associated single-stranded DNA gaps

Abstract: BRCA1 or BRCA2 (BRCA)-deficient tumor cells have defects in DNA double strand break repair by homologous recombination (HR) and fork protection (FP) that are thought to underlie the sensitivity to poly(ADP-ribose) polymerase inhibitor (PARPi). Given the recent finding that PARPi accelerates DNA replication, it was proposed that high speed DNA replication leads to DNA double strand breaks (DSBs). Here, we tested the alternative hypothesis that PARPi sensitivity in BRCA deficient cells results from combined repl… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 59 publications
(105 reference statements)
1
19
0
Order By: Relevance
“…Not surprisingly, TLS confers chemotherapy resistance, is a cancer adaptation, and is actively being targeted for cancer therapy (53,54). Moreover, we find that replication gaps due to BRCA deficiency is the basis for synthetic lethality to PARP inhibitors (55). Understanding how gap suppression functions align with other BRCA roles in genome preservation, cell viability, and tumor suppression will also be critical future questions.…”
Section: Discussionmentioning
confidence: 89%
“…Not surprisingly, TLS confers chemotherapy resistance, is a cancer adaptation, and is actively being targeted for cancer therapy (53,54). Moreover, we find that replication gaps due to BRCA deficiency is the basis for synthetic lethality to PARP inhibitors (55). Understanding how gap suppression functions align with other BRCA roles in genome preservation, cell viability, and tumor suppression will also be critical future questions.…”
Section: Discussionmentioning
confidence: 89%
“…This includes the substantially increased prevalence of ssDNA gaps following PARPi treatment in BRCA-deficient tumor cell lines, in comparison to those that were BRCA-wild type. Furthermore, significantly less ssDNA gaps were observed in PARPi resistant cell models, demonstrating that PARPi sensitivity correlates with the level of ssDNA gaps induced by PARPi treatment (Cong et al, 2019).…”
Section: Disrupted Processing Of Okazaki Fragments and Replication Fomentioning
confidence: 89%
“…This suggests an underlying mechanism of PARPi toxicity could be the result of DSBs occurring as a result of high-speed replication (Maya-Mendoza et al, 2018;Quinet and Vindigni, 2018). Based on these findings, it was also recently proposed that increased replication speed may result in the accumulation of replication-associated single-stranded DNA (ssDNA) gaps (Cong et al, 2019). It was hypothesized that these cytotoxic ssDNA gaps were attributed to PARP1's role in processing Okazaki fragments or the reversal of stalled replication forks.…”
Section: Disrupted Processing Of Okazaki Fragments and Replication Fomentioning
confidence: 99%
“…Persistent base lesions in ALC1 deficient cells may impede replication fork progression and increase the frequency of replication-coupled gaps that trap PARPi. Interestingly, several recent studies reported the accumulation of ss-DNA enriched postreplicative territories upon treatments with alkylating agents or PARPi 69,70 . Replication restart by re-priming events downstream of DNA lesion can leave ss-DNA gaps to be filled post replication 71,72 .…”
Section: Discussionmentioning
confidence: 99%